A comparison of rheumatoid arthritis in Australia and China. Issue 7 (July 1986) - Moran, H; Chen, S L; Muirden, K D; Jiang, S J; Gu, Y Y; Hopper, J; Jiang, P L; Lawler, G; Chen, R B
Abstract : A comparison was made of two series of consecutive outpatients with a presumptive diagnosis of rheumatoid arthritis (RA) attending referral centres in Melbourne and Shanghai. No significant differences were observed in disease onset, course, presence of antinuclear antibodies (ANA), or seropositivity. In the Australian series there was a higher frequency of nodules, Raynaud's phenomenon, carpal tunnel syndrome, and 'classical' in comparison with 'definite' disease, and a lower frequency of lymphadenopathy and hepatomegaly. Joint tenderness and soft tissue swelling tended to be more marked in the Chinese series, while deformity and limited range of movement were less severe. Drug therapy was similar overall but influenced by drug availability. Peptic ulceration was recorded in 28% of the Australian series but in only 6% of the Chinese; although 25% of the Chinese were receiving antacids and 6% antiulcerants. X-rays of hands and feet showed more severe disease in the Australian series. The older age group and longer duration of the disease in the Australian patients, who had more chronic and less active disease, may have influenced some of these results.